La política criminal vista desde la justicia restaurativa en México (2020)
In this article we start from the methodological point of view in terms of the scientific method in order to expand the knowledge of these concepts: the dialectical method, which aims to favor a dialogue about those issues that are of utmost importance, and several others such as the comparative, deductive, and inductive ones, provided that one of the main problems in Mexico is the high level of violence that all spheres of society are suffering. In this way, restorative justice aims to work in cooperation with criminal policy playing a fundamental role in search of a harmonious coexistence. A final hypothesis states that those of us who interact on a mutual respect basis, with human dignity reflected in reciprocal recognition and respect for the person, promote public policies that seek to deeply solve these types of problems. All these purposes are developed according to a process which guiding axis is the human being, identifying ourselves with the role played in our social group and trying to build a responsible society.